A simulation of the Boeing B-747 aircraft - Oliva, A. P. (Cranfield University, 1992)
This report describes a computer simulation model of the Boeing B-747 aircraft which is intended for use as a general purpose tool for research into advanced flight control systems for civil aircraft. The previously published model reference [1], has been adapted with little change and implemented in the Advanced Continuous Simulation Language (ACSL), for use on an appropriate personal computer. Three distinct computer models of the aircraft have been produced, a decoupled linear longitudinal model, a decoupled linear lateral-directional model and a fully coupled non-linear model. All of the aerodynamic data used in the models was obtained from reference [1] since this was considered to be the most convenient starting point. It should be noted that standard imperial units are used throughout.

This report describes a computer simulation model of the Boeing B-747 aircraft which is intended for use as a general purpose tool for research into advanced flight control systems for civil aircraft. The previously published model reference [1], has been adapted with little change and implemented in the Advanced Continuous Simulation Language (ACSL), for use on an appropriate personal computer. Three distinct computer models of the aircraft have been produced, a decoupled linear longitudinal model, a decoupled linear lateral-directional model and a fully coupled non-linear model. All of the aerodynamic data used in the models was obtained from reference [1] since this was considered to be the most convenient starting point. It should be noted that standard imperial units are used throughout.